Improvment of combined solar chimney power plant with gas power plant - Amin Mirzamohammad; Mohammad Eftekhari Yazdi; Arash Mirabdolah Lavasani (Scientific Reports, 2023)
Abstract Recently, several researches have been done to improve the perfomance of solar chimney power plants (SCPP) and increase their low output power during hours when the solar radiation is limited. In this study, by combining a SCPP and a gas power plant, the output power is increased and the power output of the combined power plant can be gained at all hours of the day and night. Pipes are buried under the ground and the outlet hot gas from gas power plant flows through the buried pipes instead of being released into the atmosphere through the stacks. Flowing of hot gas through the buried pipes at the soil under the canopy increases the temperature of soil which is exposed to the solar radiation. Increasing of the soil temperature leads to the growth in the value of air temperature under the canopy. The air density reduces as the air temperature increases which leads to the increase of air velocity and output power. By applying the buried pipes, the output power is not zero during the hours when there is no radiation flux. The results for air temperature, heat loss and output power are studied in detail and it is shown that the use of buried pipes in which hot gas flows leads to the increase of the output power of SCPP by 554%, 208% and 125% at the radiation flux of 200 W/m2, 500 W/m2 and 800 W/m2, respectively.